Video atlas of spine surgery - An, Howard S.; Louie, Philip K.; Basques, Bryce A.; Lopez, Gregory D. (Thieme, 2020)
A high-yield and comprehensive text-and-video resource for managing commonly encountered spinal conditions Spine surgery has experienced several paradigm shifts during the past few decades, with highly complex techniques introduced at an astoundingly rapid pace. In order for new generations of spine surgeons to stay current and thrive in this innovative era of spine surgery, access to diverse multimedia learning tools is imperative. Video Atlas of Spine Surgery by renowned spine surgeon and educator Howard An and Rush University Medical Center colleagues Philip Louie, Bryce Basques, and Gregor